Management of Primary Brainstem Hemorrhage: A Review of Outcome Prediction, Surgical Treatment, and Animal Model. (12th July 2022) - Chen, Peng; Yao, Haijun; Tang, Xiaoyong; Wang, Yanglingxi; Zhang, Qingtao; Liu, Yang; Hu, Jin; Deng, Yongbing
Abstract : Primary brainstem hemorrhage (PBH) has the worst prognosis of all types of intracerebral hemorrhage. Currently, the management of PBH is controversial. Hematoma classification, scoring systems, and electrophysiological monitoring are critical for predicting the outcome of PBH. Surgery may be an effective treatment for PBH. Clinical studies have emphasized the importance of animal models for understanding the pathogenesis and pathological mechanisms of PBH. In this study, combined with recent studies, the outcome prediction, surgical treatment, and animal models of PBH were reviewed.